2019
DOI: 10.15419/bmrat.v6i3.527
|View full text |Cite
|
Sign up to set email alerts
|

Determination of electrophysiological properties of human monocytes and THP-1 cells by dielectrophoresis

Abstract: Introduction: Dielectrophoresis (DEP) is based on polarization and bioparticle movement in applied electric fields. Each type of cells has its own electrical properties within the DEP spectra and undergoes significant changes in direction of frequency following an increase of an applied nonuniform alternating current (AC) electric field. Therefore, DEP can be an effective technique for characterization and separation of different cells. The goal of the current study was to determine the electrophysiological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Another study compared THP‐1 cell line monocytes and primary peripheral blood monocytes at a medium conductivity of 100 µS/cm. They found that the crossover frequencies were very different from each other: 66 and 280 kHz, respectively [30]. Another DEP characterization study of THP‐1 cells conducted in medium with conductivity of 104 µS/cm reported a crossover frequency (18.7 kHz) very close to our measurement [33].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Another study compared THP‐1 cell line monocytes and primary peripheral blood monocytes at a medium conductivity of 100 µS/cm. They found that the crossover frequencies were very different from each other: 66 and 280 kHz, respectively [30]. Another DEP characterization study of THP‐1 cells conducted in medium with conductivity of 104 µS/cm reported a crossover frequency (18.7 kHz) very close to our measurement [33].…”
Section: Discussionsupporting
confidence: 74%
“…Our results show that monocytes and mature macrophages differ in DEP properties are in general agreement with the literature. Monocyte-U937 150 20 [50] Monocyte-THP-1 Monocyte-from human blood 66 280 100 [30] Monocyte-THP-1 18.7 104 [33] used in our experiments, the crossover frequency of THP-1 monocytes was much higher than macrophage phenotypes. In contrast, the previous DEP characterization of U937-derived monocytes and macrophages at medium conductivity of 20 µS/cm by Elitas et al showed that monocytes have a lower crossover frequency (17 kHz) than macrophages (30 kHz) [31].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…According to the literature, these different DEP frequency responses of cancer and normal blood cells may be explained and expressed by Gascoyne and Shim [7] in terms of reciprocal cell "dielectric phenotype" 1/𝑅𝜙, where 𝜙 represents the membrane folding factor (the ratio of actual membrane area to that of the idealized smooth shell) and R is the cell radius. Many studies have reported that cancer cells have a larger folding factor and radii than both blood cells and normal cells of comparable origin [4,5,8,[30][31][32][33][34]. A plausible explanation could be related to an increase in the membrane cholesterol or the membrane lipid rafts in cancer cells [35,36].…”
Section: Dep-based Cells Manipulation and Electrical Impedance Spectroscopy Measurementmentioning
confidence: 99%
“…With respect to sorting and identification of various target cells, different external stimuli have been employed as an electric field in the case of electrophoresis and dielectrophoresis, a magnetic field for magnetophoresis, , a beam of light for photophoresis, , and a temperature gradient in the case of thermophoresis. Among most well-known noninvasive manipulation methods at the micro and nanoscale level, dielectrophoresis (DEP) was recognized as one of the methods with great applicability potential at the level of bioparticles such as DNA, RNA, proteins, bacteria or viruses, blood cells, rare cells including circulating tumor cells (CTCs), and stem cells, while behavior of electrical properties may be realized based on the evolution of electrical impedance determined with broadband dielectric spectroscopy (BDS). , Cancer cells characterization were not neglected by these type of studies, and a lot of cancerous cells starting from lung ,, to cervical ,, were involved in studies regarding evaluation of the electrical properties.…”
Section: Introductionmentioning
confidence: 99%